Answer:
<u><em>9 (3x+2)</em></u>
Step-by-step explanation:
<u>27x + 18 = 9 (3x+2)</u>
<em>By simplifying the Given expression you get 9 (3x+2) </em>
<em>and no matter how many times you simplify that expression you always get the expression you started with so in other word their equavalent to each other</em>
<em />
<u><em>Hope this helps</em></u>
It looks like it goes through (0,-3) and (1,2), so the gradient is (change in y)/(change in x) ->
(-3-2)/(0-1) = 5
So y=5x+b
Then as we know it passes the y axis at (0,-3) so b= -3
So we have y=5x-3
Answer:
26 2/3 minutes: The two boys meet after 26 2/3 minutes
Step-by-step explanation:
Distance covered by Jim = Distance covered by Bob
(5 mph)(t) = (8 mph)(t - 10)
Simplify this by performing the indicated multiplication:
(5 mph)(t) = (8 mph)(t) - 80 mi
or:
80 mi = (3 mph)(t), or
80 mi
t = ----------- = 26 2/3 minutes
3 mph
Answer:
its b
Step-by-step explanation:
Step-by-step explanation:
sper că te-am ajutat